2006
DOI: 10.1093/annonc/mdj007
|View full text |Cite
|
Sign up to set email alerts
|

Origins of socio-economic inequalities in cancer survival: a review

Abstract: Socio-economic differences in cancer survival are now well documented. The explanatory power of stage at diagnosis, although great, should not detract from the evidence of differential treatment between social groups. Neither factor can completely explain the observed socio-economic differences in survival, however, and the importance of differences in tumour and patient factors should now be quantified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
542
6
33

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 586 publications
(614 citation statements)
references
References 103 publications
33
542
6
33
Order By: Relevance
“…In addition, unmarried NSCLC patients are easier exposed to suicide attempts. Married patients have a greater socioeconomic status than unmarried 30, 31. Many cancer research studies have reported a poor prognosis in unmarried patients 32, 33, 34…”
Section: Discussionmentioning
confidence: 99%
“…In addition, unmarried NSCLC patients are easier exposed to suicide attempts. Married patients have a greater socioeconomic status than unmarried 30, 31. Many cancer research studies have reported a poor prognosis in unmarried patients 32, 33, 34…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the uptake of screening, 22 stage at diagnosis, 3 level of comorbidity 23,24 and access to optimal treatment 25 are all potential explanations for the difference in cancer survival between rich and poor patients. Whilst differences in stage at diagnosis and comorbidity have explained only a small proportion of the socioeconomic disparities in survival from colorectal cancer, 26 differential access to healthcare has been shown to strongly influence these inequalities in survival.…”
Section: Discussionmentioning
confidence: 99%
“…2 The percentage of avoidable deaths is the number of avoidable deaths as a proportion of all excess deaths 3 The number of avoidable deaths partly depends on the deficit in relative survival between affluent and deprived groups. If survival for a particular cancer is higher in deprivation categories 2-5 than the most affluent category (1), the number and proportion of avoidable deaths can be negative.…”
Section: Conflict Of Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many countries, cancer outcomes are better in women and men with high compared to low socioeconomic status (SES) 1, 2. This association has also been observed in Sweden, a country with a tax‐financed national health care system aiming to provide care on equal terms to all residents 3, 4, 5…”
mentioning
confidence: 83%